2001
DOI: 10.1038/35051113
|View full text |Cite
|
Sign up to set email alerts
|

ICOS is essential for effective T-helper-cell responses

Abstract: The outcome of T-cell responses after T-cell encounter with specific antigens is modulated by co-stimulatory signals, which are required for both lymphocyte activation and development of adaptive immunity. ICOS, an inducible co-stimulator with homology to CD28, is expressed on activated, but not resting T cells, and shows T-cell co-stimulatory function in vitro. ICOS binds specifically to its counter-receptor B7RP-1 (refs 5,6,7), but not to B7-1 or B7-2. Here we provide in vivo genetic evidence that ICOS deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
482
4
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 620 publications
(515 citation statements)
references
References 28 publications
28
482
4
1
Order By: Relevance
“…The IL-10-secreting phenotype was stably maintained during T cell cloning, but secretion was, to a large extent, dependent on ICOS signaling, which is in agreement with previous reports [28][29][30][31]. Of note, studies in ICOS-deficient mice have revealed a key role for this costimulatory molecule in Tdependent B cell responses [24,25]. Together, these observations suggest that the ability of ICOS to support IL-10 production by T cells plays a critical role in the provision of help to B cells.…”
Section: Discussionsupporting
confidence: 90%
“…The IL-10-secreting phenotype was stably maintained during T cell cloning, but secretion was, to a large extent, dependent on ICOS signaling, which is in agreement with previous reports [28][29][30][31]. Of note, studies in ICOS-deficient mice have revealed a key role for this costimulatory molecule in Tdependent B cell responses [24,25]. Together, these observations suggest that the ability of ICOS to support IL-10 production by T cells plays a critical role in the provision of help to B cells.…”
Section: Discussionsupporting
confidence: 90%
“…In summary, these observations demonstrate the role of a novel TNF/TNFR partner in the current models of the kinetic dynamics of human B cell stimulation and differentiation proposed by Morimoto et al [14], in addition to the other TNF/TNFR family members CD40/CD40L, CD27/CD70 and CD134/CD134L and ICOS [7,8]. Regarding the model proposed by Morimoto et al [14], LIGHT participates in the first step, i.e.…”
Section: Light Stimulation Enhances Ig Secretionsupporting
confidence: 65%
“…ICOS is expressed on both CD4 + and CD8 + activated T lymphocytes [6]. ICOS is essential for T cell-dependent B cell responses [7][8][9] and the GC reactions [10,11]. The mechanism underlying B cell activation by ICOS may, at least partially, function through the CD40/CD40L pathway [12].…”
Section: Light Stimulation Enhances Ig Secretionmentioning
confidence: 99%
“…Of the costimulatory molecules we assessed, ICOS was the one most strongly up-regulated on activated CXCR5 + CD8 T cells. In mice, a lack of ICOS results in severely deficient T cell-dependent B cell responses with impaired GC formation and Ig class switching [41]. Thus, ICOS fulfills a non-redundant function in the interaction between T and B cells.…”
Section: Discussionmentioning
confidence: 99%